PERAN PEMERINTAH DAERAH PROPINSI KALIMANTAN BARAT DALAM PENGEMBANGAN SISTEM TRANSPORTASI AIR TERKAIT DENGAN PEMBERIAN IZIN TRAYEK/IZIN OPERASIONAL BAGI KAPAL PEDALAMAN LINTAS KABUPATEN/KOTA. - JASMAN,S.St.Pi A.202113010, Jurnal Mahasiswa S2 Hukum UNTAN (Jurnal NESTOR Magister Hukum, 2016)
ABSTRACTThis thesis discusses the role of the local government of West Kalimantan Province in the development of water transport systems associated with the provision of route permits / operating permit for inland vessels inland across districts / cities. From the research we concluded that: Transportrasi River has the potential to be developed in West Kalimantan. Tranportrasi development in the Kapuas River, West kaimantan require a comprehensive study to look at the various aspects that are at the Kapuas river, such as: laulintas conditions, traffic volume, passenger characteristics, ownership of transport operations, condition of physical infrastructure transportrasi, and institutional transport air.Pelaksanaan granting route permits / operating permit for inland vessels cross the Regency / City in West Kalimantan conducted in accordance with Kepmenhub KM. 73 Year 2004 Jo Permenhub No. 58 of 2007, and West Kalimantan Provincial Regulation No. 9 of 2007, where the licensing authority in the hands of the Governor. While the Port Administrator authority concerns only ships that pass through the sea, not including transport stream, lake and ferry.Factors affecting the implementation of the licensing route / operational licenses for inland vessels cross the Regency / City in West Kalimantan is associated with the authority of the Port Administration, among others: Because of the geographical area between the Rasau jaya with Trunk Bay across the river and the sea, Each party has not understood authorities in accordance with the provisions of, and lack of coordination between the Department of Transportation, Communications and Information Technology of West Kalimantan Province with Port Administrator / Administrative Office Pelabuhan.Upaya carried out by agencies of the overlap in the provision of route permits / operating permit for inland vessels cross regencies / cities in Kalimantan West, is to: Conduct coordination meetings with related agencies and associations Gapasdap (Association of Transport River Lake Crossing), Conducting socialization to entrepreneurs / owners of inland vessels if there are rules that new, Monitoring of the condition of the infrastructure continuously , increase the knowledge and skills of human resources in the field of transport streams, lakes and crossings and Conduct a review on the ground and examine issues of conflict.Keywords: systems development, water transport, and licensingABSTRAKTesis ini membahas peran pemerintah daerah Propinsi Kalimantan Barat dalam pengembangan sistem transportasi air terkait dengan pemberian izin trayek/izin operasional bagi kapal pedalaman pedalaman lintas kabupaten/kota. Dari hasil penelitian diperoleh kesimpulan, bahwa :Transportrasi Sungai sangat berpotensi untuk dikembangkan di Kalimantan Barat. Pengembangan tranportrasi di sungai Kapuas, Kaimantan Barat memerlukan studi yang komprehensif dengan melihat berbagai aspek yang berada pada sungai kapuas, seperti: kondisi laulintas, volume lalu-lintas, karakteristik penumpang, kepemilikan operasi angkutan, kondisi prasarana fisik transportrasi, serta kelembagaan angkutan air.Pelaksanaan Pemberian izin trayek/izin operasional bagi kapal pedalaman lintas Kabupaten/Kota di Kalimantan Barat dilaksanakan sesuai dengan Kepmenhub Nomor KM. 73 Tahun 2004 Jo Permenhub Nomor 58 Tahun 2007, dan Peraturan Daerah Provinsi Kalimantan Barat Nomor 9 Tahun 2007, di mana kewenangan pemberian izin berada di tangan Gubernur. Sedangkan kewenangan Administrator Pelabuhan hanya menyangkut kapal-kapal yang melewati laut saja, tidak termasuk angkutan sungai, danau, dan penyeberangan.Faktor yang mempengaruhi pelaksanaan pemberian izin trayek/izin operasional bagi kapal pedalaman lintas Kabupaten/Kota di Kalimantan Barat dikaitkan dengan kewenangan Administrator Pelabuhan, antara lain: Karena faktor geografis Wilayah antara Rasau jaya dengan Teluk Batang melintasi sungai dan laut, Masing-masing pihak belum memahami kewenangan sesuai dengan ketentuan, dan Kurangnya koordinasi antara Dinas Perhubungan, Komunikasi dan Informatika Provinsi Kalbar dengan Administrator Pelabuhan/Kantor Administrasi Pelabuhan.Upaya yang dilakukan oleh instansi terhadap tumpang tindih dalam pemberian izin trayek/izin operasional bagi kapal pedalaman lintas Kabupaten/Kota di wilayah Kalimantan Barat, adalah dengan: Melakukan rapat-rapat koordinasi dengan Instansi terkait dan Asosiasi Gapasdap (Gabungan Pengusaha Angkutan Sungai, Danau dan Penyeberangan), Melakukan sosialisasi kepada Pengusaha/pemilik kapal pedalaman bila ada peraturan-peraturan yang baru, Melakukan monitoring tentang kondisi prasarana secara kontinue, Meningkatkan pengetahuan dan keterampilan SDM di bidang angkutan sungai, danau dan penyeberangan dan Melakukan peninjauan di lapangan dan mengkaji masalah yang menjadi konflik.